Source spectra of the gravity waves obtained from momentum flux and kinetic energy over Indian region: Comparison between observations and model results. (February 2017) - Pramitha, M.; Venkat Ratnam, M.; Krishna Murthy, B.V.; Vijaya Bhaskar Rao, S.
Abstract: Using 8 years (May 2006 to March 2014) of high resolution and high accuracy GPS radiosonde observations available from a tropical station Gadanki (13.5°N, 79.2°E), India, we have investigated the climatology of gravity wave energy and zonal momentum fluxes in the lower stratosphere. We also obtained best fit spectrum model for the gravity waves (GWs) for this tropical station. In general, strong annual variation in the energy and momentum flux with maximum during Indian summer monsoon is observed in the lower stratospheric region (18–25 km). By considering different source spectra, we have applied Gravitywave Regional or Global RAy Tracer (GROGRAT) model run on monthly basis using the source spectrum values at different altitudes on the ERA-Interim background fields to obtain the kinetic energy and zonal momentum fluxes for each of the spectra considered. These simulated fluxes are compared with the observed fluxes to arrive at the best fit spectrum model. It is found that the spectrum which represents the convection transient mountain mechanism that is purely anti-symmetric and anisotropic in nature is the best fit model for Gadanki location. This information would be useful in parameterization of the GWs in numerical models over Indian region. Highlights: The climatology of GW energy and zonal momentum flux in the lower stratosphere for the tropical region is obtained. Strong annual variation in the energy and MF with maximum during Indian summer monsoon in the lower stratospheric region (18–25 km). The convection transient mountain mechanism (purely anti-symmetric and anisotropic) is found the best fit model. This information would be useful in parameterization of the GWs in the numerical models.